2020
DOI: 10.1038/s41564-020-0672-6
|View full text |Cite
|
Sign up to set email alerts
|

Envelope stress responses defend against type six secretion system attacks independently of immunity proteins

Abstract: The arms race among microbes is a key driver in the evolution of not only the weapons but also defence mechanisms. Many gram-negative bacteria use the type six secretion system (T6SS) to deliver toxic effectors directly into neighbouring cells. Defence against effectors requires cognate immunity proteins. However, here we show immunity-independent protection mediated by envelope stress responses in Escherichia coli and Vibrio cholerae against a V. chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(175 citation statements)
references
References 58 publications
7
159
1
Order By: Relevance
“…Besides RS factors, recent studies have revealed the presence of immunity-independent resistance in recipient cell that were nicely reviewed by Robitaille et al (2020). These recipient defense factors or mechanisms include physical barriers such as exopolysaccharide (Toska et al, 2018), envelope stress responses (Hersch et al, 2020), or peptidoglycan editing (Le et al, 2020). Growing evidence of the involvement of recipient factors in either enhancing T6SS toxicity or defense against T6SS indicates an evolutionary arms race during interbacterial competition, which may play roles in shaping microbiome.…”
Section: A Tumefaciens Type VI Secretion System Killingmentioning
confidence: 99%
“…Besides RS factors, recent studies have revealed the presence of immunity-independent resistance in recipient cell that were nicely reviewed by Robitaille et al (2020). These recipient defense factors or mechanisms include physical barriers such as exopolysaccharide (Toska et al, 2018), envelope stress responses (Hersch et al, 2020), or peptidoglycan editing (Le et al, 2020). Growing evidence of the involvement of recipient factors in either enhancing T6SS toxicity or defense against T6SS indicates an evolutionary arms race during interbacterial competition, which may play roles in shaping microbiome.…”
Section: A Tumefaciens Type VI Secretion System Killingmentioning
confidence: 99%
“…A recent publication described that E. coli and Vibrio cholerae can mount an immunity-independent resistance against type VI-secretion system via envelope stress response modulators – Rcs phosphorelay ( E. coli ) and two-component systems BaeSR ( E. coli ) and WigKR ( V. cholerae ). Authors showed that responses include such phenotypes as up-regulation of osmotic-response genes, increased capsular polysaccharide synthesis, and general cell integrity preservation ( Hersch et al, 2020 ). It is tempting to speculate, that BfmRS system might similarly cause immunity-independent resistance phenotype against CDI as in addition to the role in capsule formation in some A. baumannii strains, it also contributes to resistance to high osmolarity and desiccation ( Farrow et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such physical protection stands in stark contrast to active, species-dependent defence mechanisms that are controlled genetically [36,38,40,41]. Physical barriers represent an emergent first line of defence that do not require active sensing or control and are species independent.…”
Section: Discussionmentioning
confidence: 99%